The use of virtual reality for balance among individuals with chronic stroke: a systematic review and meta-analysis. Issue 1 (2nd January 2017) - Iruthayarajah, Jerome; McIntyre, Amanda; Cotoi, Andreea; Macaluso, Steven; Teasell, Robert
Abstract : Background: Virtual reality (VR) is becoming a popular alternative to traditional upper and lower limb rehabilitation following a stroke. Objective: To conduct a systematic review and meta-analysis on the effectiveness of VR interventions for improving balance in a chronic stroke (≥6 months) population. Data sources: A literature search of Pubmed, Scopus, CINAHL, Embase, Psycinfo, and Web of Science databases was conducted. Study selection: English randomized controlled trials published up to September 2015 assessing balance with VR in chronic stroke participants. Data extraction: Mean and standard deviations from outcome measures were extracted. Pooled standard mean differences ± standard error were calculated for the Berg Balance Scale (BBS) and the Timed Up and Go test (TUG). Results: In total, 20 studies were selected which assessed the Nintendo ® Wii Fit balance board ( n  = 7), treadmill training and VR ( n  = 7), and postural training using VR ( n  = 6). Significant improvements were found for VR interventions evaluating the BBS ( n  = 12; MD = 2.94 ± 0.57; p  < 0.001) and TUG ( n  = 13; MD = 2.49 ± 0.57; p  < 0.001). Sub-analyses revealed postural VR interventions had a significant effect on BBS ( n  = 5) and TUG ( n  = 3) scores (BBS: MD = 3.82 ± 0.79; p  < 0.001 and TUG: MD = 3.74 ± 0.97; p  < 0.001). VR and treadmill training ( n  = 5) had a significant effect on TUG scores (MD = 2.15 ± 0.89, p  = 0.016). Conclusion: Overall, VR interventions compared to conventional rehabilitation had significant improvements. The meta-analyses also suggest that the Nintendo ® Wii Fit balance board may not be effective, although further confirmatory studies are necessary. Results should be interpreted with caution due to differences in therapy intensities and effect sizes within the included studies.